Associations Between Copays, Coverage Limits for Naloxone, and Prescribing in Medicaid - John C Messinger; Aaron S Kesselheim; Seanna M Vine; Michael A Fischer; Rachel E Barenie (SAGE Publishing, 2022)
Aims: To describe naloxone dispensing in Medicaid fee-for-service (FFS) and examine relationships between copays and coverage limits for naloxone and its dispensing rates. Methods: Cross-sectional study using Medicaid FFS State Drug Utilization Data to quantify the use of naloxone in 2018. The primary outcomes of this study were the proportion of naloxone prescriptions relative to all prescriptions and all opioid prescriptions dispensed in each state. We obtained drug benefit design information from the Medicaid Behavioral Health Services Database. The primary analysis examined the influence of copays (yes/no), copay amounts, and coverage limits on medication dispensing using simple linear regression, excluding states with no measurable use or less than 5% Medicaid FFS. Results: We found substantial variability across 50 states and DC in the proportion of prescriptions dispensed for Narcan and generic naloxone. We found a positive relationship between copay and copay amount and dispensing of generic naloxone. However, a sensitivity analysis including the broadest possible cohort of states failed to confirm this relationship. We found no other relationships between copays or coverage limits and dispensing of any naloxone formulation. Conclusions: Substantial variation exists between the rates of naloxone dispensing across the US for Medicaid patients, but we did not find a meaningful relationship between plan design and dispensing. Whether drug benefit designs in Medicaid influence naloxone use requires further evaluation to avoid limiting access to this life-saving medication.